2018
DOI: 10.1016/j.immuni.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Interferons and Proinflammatory Cytokines in Pregnancy and Fetal Development

Abstract: Successful pregnancy requires carefully-coordinated communications between the mother and fetus. Immune cells and cytokine signaling pathways participate as mediators of these communications to promote healthy pregnancy. At the same time, certain infections or inflammatory conditions in pregnant mothers cause severe disease and have detrimental impacts on the developing fetus. In this review, we examine evidence for the role of maternal and fetal immune responses affecting pregnancy and fetal development, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
371
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(393 citation statements)
references
References 176 publications
14
371
0
8
Order By: Relevance
“…Other studies have also shown a correlation between poor pregnancy outcomes and the concentrations of systemic cytokines, including TNF-α, IFNγ, and IL-10 in women with malaria (Fried et al, 2017). Abnormally elevated levels of TNF-α in the maternal peripheral blood can be toxic to early embryo development, induces preterm labor in non-human primate models, and mediates fetal demise in mouse models of LPS and poly(I:C)-induced fetal resorption (Yockey et al, 2018). Moreover, the most common symptom at the onset of COVID-19 infection is the fever, which could be associated with increased attention-deficit/hyperactivity disorder in the offspring (Werenberg et al, 2016).…”
Section: The Role Of Maternal Immune Responses To Covid-19mentioning
confidence: 99%
“…Other studies have also shown a correlation between poor pregnancy outcomes and the concentrations of systemic cytokines, including TNF-α, IFNγ, and IL-10 in women with malaria (Fried et al, 2017). Abnormally elevated levels of TNF-α in the maternal peripheral blood can be toxic to early embryo development, induces preterm labor in non-human primate models, and mediates fetal demise in mouse models of LPS and poly(I:C)-induced fetal resorption (Yockey et al, 2018). Moreover, the most common symptom at the onset of COVID-19 infection is the fever, which could be associated with increased attention-deficit/hyperactivity disorder in the offspring (Werenberg et al, 2016).…”
Section: The Role Of Maternal Immune Responses To Covid-19mentioning
confidence: 99%
“…Innate immunity is not compromised during pregnancy in swine and humans, despite an increase in regulatory and Th2 cytokines like TGF-β, IL-4, and IL-10 in the second trimester [77,78]. Indeed, innate immune parameters like type I and II IFNs and acute phase proinflammatory cytokines are integral to the success of early pregnancy in swine and humans [79][80][81]. Additionally, studies of pregnant women suggest that innate immune cells are actually more responsive to stimuli than in nonpregnant women.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Indeed, manipulation of NFKB subunits in a diverse range of animal models results in severe developmental defects during embryogenesis, often leading to embryonic lethality. NFKB had been proposed as a mediator of epithelial–mesenchymal interactions (for review, see Espín‐Palazón & Traver, ; Yockey & Iwasaki, ), which justifies this broad range of developmental effects and warrants further studies to understand its role in the Wolffian duct.…”
Section: Innate Immunity Fetal Development and Reproductive Healthmentioning
confidence: 99%